Antidepressants versus placebo in major depression: an overview - Khan, Arif (World Psychiatry, 2015)
Although the early antidepressant trials which included severely ill and hospitalized patients showed substantial drug-placebo differences, these robust differences have not held up in the trials of the past couple of decades, whether sponsored by pharmaceutical companies or non-profit agencies. This narrowing of the drug-placebo difference has been attributed to a number of changes in the conduct of clinical trials. First, the advent of DSM-III and the broadening of the definition of major depression have led to the inclusion of mildly to moderately ill patients into antidepressant trials. These patients may experience a smaller magnitude of antidepressant-placebo differences. Second, drug development regulators, such as the U.S. Food and Drug Administration and the European Medicines Agency, have had a significant, albeit underappreciated, role in determining how modern antidepressant clinical trials are designed and conducted. Their concerns about possible false positive results have led to trial designs that are poor, difficult to conduct, and complicated to analyze. Attempts at better design and patient selection for antidepressant trials have not yielded the expected results. As of now, antidepressant clinical trials have an effect size of 0.30, which, although similar to the effects of treatments for many other chronic illnesses, such as hypertension, asthma and diabetes, is less than impressive.